Aggressive Hydration With Lactated Ringer Solution in Prevention of Postendoscopic Retrograde Cholangiopancreatography Pancreatitis: A Meta-analysis of Randomized Controlled Trials. Issue 3 (March 2017) - Zhang, Zhi-Feng; Duan, Zhi-Jun; Wang, Li-Xia; Zhao, Gang; Deng, Wu-Guo
Abstract : Background: Pancreatitis is the most common complication of endoscopic retrograde cholangiopancreatography (ERCP). The results of previous studies evaluating aggressive hydration with lactated Ringer solution for reducing the incidence of post-ERCP pancreatitis (PEP) are inconsistent. Aim: We performed a meta-analysis to determine whether aggressive hydration with lactated Ringer solution reduced PEP. Methods: Randomized controlled trials (RCTs) comparing aggressive hydration with standard hydration with the same lactated Ringer solution for prophylaxis of PEP were searched in PubMed, Embase, Cochrane Central Register of Controlled Trials (CENTRAL), and CINAHL databases. ClinicalTrial.gov and International Standard Randomised Controlled Trial Number registry were also searched for unpublished studies. A meta-analysis was conducted in accordance with the Cochrane Handbook for Systemic Reviews of Intervention. Results: A total of 7 RCTs with 1047 participants were included into this meta-analysis. Meta-analysis showed that aggressive hydration reduced the incidence of PEP as compared with standard hydration [odds ratio (OR), 0.47; 95% confidence interval (CI), 0.30-0.72; P =0.0006]. Aggressive hydration also reduced the incidence of post-ERCP hyperamylasemia as compared with standard hydration (OR, 0.38; 95% CI, 0.25-0.59; P <0.00001). No difference of adverse effects was found between aggressive hydration and standard hydration (OR, 0.48; 95% CI, 0.15-1.57; P =0.23). Sensitivity analyses showed that neither alternative effect measures nor statistical models regarding heterogeneity affected the conclusions of this meta-analysis. Sensitivity analyses also showed that omitting 1 study from analysis did not change the conclusion of this meta-analysis. Conclusions: On the basis of this meta-analysis of RCTs, aggressive hydration with lactated Ringer solution is an effective and safe therapy for prophylaxis of PEP. Abstract : Supplemental Digital Content is available in the text.